Method for removing nitrate in drilling and blasting method tunnel construction wastewater

PAN nanofibers were prepared by electrospinning, combined with calcium-based montmorillonite adsorption and zero-valent iron reduction, and solved the problem of excessive nitrate nitrogen in the drilling and explosion tunnel construction wastewater, achieving efficient and low-cost nitrate removal. It is easy to operate and inexpensive, and is recycled and utilized.

CN119263396AActive Publication Date: 2025-01-07CHINA RAILWAY ENVIRONMENTAL TECH ENG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411497608.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

There is a problem of nitrate nitrogen exceeding the standard in the drilling and explosion tunnel construction wastewater, and the existing technology is difficult to remove nitrate efficiently and at low cost.

Method used

Electrospinning is used to prepare PAN nanofibers, using calcium-based montmorillonite adsorption and zero-valent iron reduction, combined with nanofiber materials, remove nitrates in water and generate harmless nitrogen.

Benefits of technology

It realizes efficient and low-cost removal of ammonia nitrogen and total nitrogen in the drilling and explosion tunnel construction wastewater, which is easy to operate, low cost, and can recycle PAN substrate materials, reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263396A_ABST
    Figure CN119263396A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing nitrate in drilling and blasting method tunnel construction wastewater, which comprises the following steps: 1, preparing electrostatic spinning nanofibers: firstly, adding DMF (Dimethyl Formamide) into a container, sequentially adding submicron iron powder and submicron calcium-based montmorillonite into a DMF solution, and carrying out ultrasonic dispersion to obtain the electrostatic spinning nanofibers; then stirring to uniformly disperse the iron powder and the calcium-based montmorillonite; weighing PAN powder, adding the PAN powder into the solution, and stirring until the PAN powder is completely dissolved into viscous liquid; then putting the obtained solution into an electrostatic spinning machine for electrostatic spinning to prepare PAN nanofibers; 2, nitrate in drilling and blasting method tunnel construction wastewater is removed, specifically, the prepared PAN nanofiber is completely soaked in the drilling and blasting method tunnel construction wastewater for a period of time, and then the PAN nanofiber is taken out. According to the method, nitrate in the drilling and blasting method tunnel construction wastewater can be efficiently removed at low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment in tunnel construction using a drilling and blasting method, and in particular relates to a method for removing nitrates in wastewater from tunnel construction using a drilling and blasting method. Background Art

[0002] The main components of explosives used in tunnel drilling and blasting construction, such as emulsion explosives or TNT, are NH 4 NO 3 , or 1,3,5-trinitrotoluene, which results in the presence of a certain amount of ammonia nitrogen, nitrate nitrogen, etc. in the tunnel construction wastewater. It is a micro-polluted water with high SS and high alkalinity. Generally, the content of ammonia nitrogen and nitrate nitrogen will not exceed the standard. However, in ecologically sensitive areas, when the discharge implements the Class III standard in the "Surface Water Environmental Quality Standard" (GB3838-2002), the ammonia nitrogen and nitrate nitrogen may exceed the standard requirements.

[0003] Due to the low concentration of organic matter in wastewater, it is not suitable to rely on biochemical treatment processes to remove nitrate nitrogen, and the removal of nitrate is a major difficulty.

[0004] The zero-valent metal reduction method has the advantages of low cost, simple management and high efficiency. However, this method may produce secondary pollutants to pollute water bodies. Therefore, it is necessary to develop an efficient and low-cost nitrate removal method. Summary of the invention

[0005] The purpose of the present invention is to provide a method for removing nitrates in wastewater from tunnel construction by drilling and blasting method, so as to solve the problem in the background technology that nitrate nitrogen in wastewater from tunnel construction by drilling and blasting method may exceed the standard but there is a lack of efficient and low-cost removal methods.

[0006] To achieve the above object, the present invention provides a method for removing nitrates from wastewater in tunnel construction by drilling and blasting method, comprising the following steps:

[0007] Step 1, preparing electrospinning nanofibers: using DMF (N, N-dimethylformamide) as the solvent of the nanofiber precursor and PAN (polyacrylonitrile) as the electrospinning base material, first taking DMF and adding it into a container, and taking submicron iron powder and submicron calcium-based montmorillonite, the mass ratio of iron powder and calcium-based montmorillonite is 1 to 9:3, and adding them into the DMF solution in sequence, and ultrasonically dispersing, and then stirring to make the iron powder and calcium-based montmorillonite evenly dispersed; weighing PAN powder, adding it to the above solution, stirring, so that PAN is completely dissolved into a viscous liquid, that is, obtaining an electrospinning precursor solution, the mass fraction of PAN in the electrospinning precursor solution is 5 to 15%, and then putting the obtained solution into an electrospinning machine for electrospinning to prepare PAN nanofibers, drying the prepared PAN nanofibers, removing excess DMF, and preventing the PAN nanofibers from sticking;

[0008] Step 2, removing nitrates from wastewater from tunnel construction using the drilling and blasting method: completely immersing the dried PAN nanofibers in the wastewater from tunnel construction using the drilling and blasting method, and taking out the PAN nanofibers after immersing for a period of time.

[0009] In a specific embodiment, the method for removing nitrates from tunnel construction wastewater by the drilling and blasting method further includes step 3, recycling of PAN: soaking the used PAN nanofibers in dilute hydrochloric acid to remove excess iron powder, then drying them in an oven, and then placing the dried PAN nanofibers in a ball mill for grinding. After the ball milling is completed, the PAN powder is ground and separated and sieved, thereby completing the recycling of PAN.

[0010] In a specific embodiment, in the step 1, the drying temperature of the prepared PAN nanofibers in the oven is 80° C.; in the step 3, the drying temperature of the used PAN nanofibers in the oven is 80° C., and the drying time is 10 hours.

[0011] In a specific implementation, in step 3, when the material is put into a ball mill for grinding, the speed of the ball mill is set to 200-400 r / min, the ball-to-material ratio is set to 50-150:1, and the ball milling time is set to 5-15 min.

[0012] In a specific embodiment, in step 1, the mass ratio of DMF: iron powder: calcium-based montmorillonite is 17-19:1:1.

[0013] In a specific embodiment, in step 1, the mass ratio of the added amount of PAN powder to the sum of the mass of iron powder and calcium-based montmorillonite is 0.5-1.5:1.

[0014] In a specific embodiment, in step 1, the voltage of the electrospinning machine is set to 15-25 kV, the propulsion speed is set to 0.01-0.03 mL / min, the receiving distance is set to 10-20 cm, and the roller speed is set to 200-500 r / min.

[0015] In a specific embodiment, in step 1, stirring is performed for 0.5 to 2 hours after ultrasonic dispersion, and stirring is performed for 4 to 16 hours after adding PAN powder.

[0016] In a specific embodiment, in step 2, the soaking time is 6 to 18 hours.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The invention can remove ammonia nitrogen and total nitrogen in wastewater from tunnel construction using the drilling and blasting method with high efficiency and low cost.

[0019] The present invention skillfully utilizes nanofiber materials, and adopts a combination of iron powder and calcium-based montmorillonite in an optimal mass ratio in the preparation of the nanofiber materials, thereby achieving an optimal removal effect on nitrate ions.

[0020] The present invention creatively combines the adsorption effect of calcium-based montmorillonite with the reduction effect of zero-valent iron. The calcium-based montmorillonite adsorbs and enriches nitrate ions, and generates harmless nitrogen gas under the reduction effect of zero-valent iron, thereby reducing the nitrate concentration in the water body.

[0021] Compared with other methods for removing nitrate, the present invention has the advantages of simple operation and low cost.

[0022] The PAN substrate material used in the present invention can also be recycled after powder screening, thereby further reducing the cost.

[0023] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention is further described in detail below. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0025] Figure 1 is a graph of nitrate removal efficiency of nanofibers with different mass ratios of iron powder and calcium-based montmorillonite;

[0026] Figure 2 is a graph of nitrate removal rate and PAN recovery rate for comparative examples and different embodiments;

[0027] Figure 3 This is a scanning electron microscope image of PAN nanofibers. DETAILED DESCRIPTION

[0028] The embodiments of the present invention are described in detail below. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] A method for removing nitrate from wastewater from tunnel construction using a drilling and blasting method according to the present invention comprises the following steps:

[0030] Step 1, preparing electrospinning nanofibers: using DMF (N, N-dimethylformamide) as a solvent for nanofiber precursors and PAN (polyacrylonitrile) as an electrospinning base material, first taking DMF and adding it to a container, and taking submicron iron powder and submicron calcium-based montmorillonite, the mass ratio of iron powder to montmorillonite is 1 to 9:3, and adding them to the DMF solution in sequence, and ultrasonically dispersing, and then stirring to make the iron powder and montmorillonite evenly dispersed; weighing PAN powder, adding it to the above solution, stirring, so that PAN is completely dissolved into a viscous liquid, that is, obtaining an electrospinning precursor solution, the mass fraction of PAN in the electrospinning precursor solution is 5-15%; then putting the obtained solution into an electrospinning machine for electrospinning to prepare PAN nanofibers, drying the prepared PAN nanofibers, removing excess DMF, and preventing the PAN nanofibers from sticking;

[0031] The particle size of the submicron iron powder is 0.5-10 μm, the particle size of the submicron calcium-based montmorillonite is 2-8 μm, and preferably the average particle size of the submicron calcium-based montmorillonite is 4 μm. The mass ratio of the iron powder to the montmorillonite is preferably 1:1.

[0032] Step 2, removing nitrates from wastewater from tunnel construction using the drilling and blasting method: completely immersing the dried PAN nanofibers in the wastewater from tunnel construction using the drilling and blasting method, and taking out the PAN nanofibers after immersing for a period of time.

[0033] The method for removing nitrate from wastewater from tunnel construction by drilling and blasting also includes step 3, recycling PAN: soaking the used PAN nanofibers in dilute hydrochloric acid to remove excess iron powder, then drying them in an oven, and then putting the dried PAN nanofibers into a ball mill for grinding. After the ball milling is completed, the PAN powder is ground and separated and sieved, thereby completing the recycling of PAN.

[0034] In the step 1, the prepared PAN nanofibers are dried in an oven at a temperature of 80° C.; in the step 3, the used PAN nanofibers are dried in an oven at a temperature of 80° C. for a drying time of 10 hours.

[0035] In the step 3, when the material is put into a ball mill for grinding, the speed of the ball mill is set to 200-400 r / min, the ball-to-material ratio is set to 50-150:1, and the ball milling time is set to 5-15 min; preferably, the ball milling time is set to 10 min.

[0036] In the step 1, the mass ratio of DMF: iron powder: calcium-based montmorillonite is 17-19:1:1.

[0037] In the step 1, the mass ratio of the added amount of PAN powder to the sum of the mass of iron powder and calcium-based montmorillonite is 0.5-1.5:1.

[0038] In the step 1, the voltage of the electrospinning machine is set to 15-25 kV, the propulsion speed is set to 0.01-0.03 mL / min, the receiving distance is set to 10-20 cm, and the roller speed is set to 200-500 r / min; preferably, the voltage of the electrospinning machine is set to 20 kV, the propulsion speed is preferably set to 0.02 mL / min, the receiving distance is preferably set to 15 cm, and the roller speed is preferably set to 300 r / min.

[0039] In the step 1, the mixture is stirred for 0.5 to 2 hours after ultrasonic dispersion, and stirred for 4 to 16 hours after the addition of PAN powder; preferably, the mixture is stirred for 1 hour after ultrasonic dispersion, and stirred for 8 hours after the addition of PAN powder.

[0040] In step 2, the soaking time is 6 to 18 hours.

[0041] The TN (total nitrogen) concentration of a water conservancy tunnel construction wastewater was 21.69 mg / L, and NO 3- The concentration is 12.42 mg / L. The wastewater was treated with nanofibers with different mass ratios of iron powder and calcium-based montmorillonite. The nitrate removal rate was as follows Figure 1 shown.

[0042] Example 1

[0043] First, 9g of DMF was added to a beaker, and 0.5g of submicron iron powder and 0.5g of submicron calcium-based montmorillonite were added to the DMF solution in turn, and ultrasonically dispersed, and then stirred for 1h to uniformly disperse the iron powder and calcium-based montmorillonite. 1g of PAN white powder was weighed and added to the above solution, and stirred for 8h to completely dissolve PAN into a viscous liquid, thereby obtaining an electrospinning precursor solution, wherein the mass fraction of PAN was 10%. The electrospinning precursor solution was then placed in an electrospinning machine for electrospinning, and electrospinning was performed for 12h under the conditions of voltage 20kV, propulsion speed 0.02mL / min, receiving distance 15cm, and roller speed 300r / min to obtain PAN nanofibers, and the prepared PAN nanofibers were dried to remove excess DMF to prevent PAN nanofiber adhesion, thereby completing the preparation of PAN nanofibers. The dried PAN nanofibers were completely immersed in the wastewater from the drilling and blasting tunnel construction, and the PAN nanofibers were used to remove nitrates. The immersion time was 12 hours. After the reaction was completed, the PAN nanofibers were taken out.

[0044] The PAN nanofibers that have adsorbed nitrate ions are first soaked in dilute hydrochloric acid to remove excess iron powder, and then dried in an oven at 80°C for 10 hours. The dried PAN nanofibers are then placed in a ball mill for grinding, wherein the ball mill speed is 300 r / min, the ball-to-material mass ratio is 100:1, and the ball milling time is 10 minutes. After the ball milling is completed, the PAN powder is separated and sieved through a 200-mesh sieve to complete the recycling of PAN.

[0045] like Figure 1 As shown in Figure 2, the addition of calcium-based montmorillonite and iron powder is beneficial to the removal of nitrate, and the optimal mass ratio of iron powder to calcium-based montmorillonite is 1:1. Figure 2 It can be seen that the above method can remove nitrate from water with a high nitrate removal rate, and after recovery by the above method, there is also a high PAN recovery rate, indicating that the material prepared in Example 1 has good performance.

[0046] Comparative Example 1

[0047] First, 9.6g DMF was added to a beaker, and 0.5g of submicron iron powder and 0.5g of submicron calcium montmorillonite were added to the DMF solution in turn, and ultrasonically dispersed, and then stirred for 1h to uniformly disperse the iron powder and calcium montmorillonite. 0.4g PAN white powder was weighed and added to the above solution, and stirred for 8h to completely dissolve PAN into a viscous liquid, and an electrospinning precursor solution was obtained, wherein the mass fraction of PAN was 4%. The electrospinning precursor solution was then placed in an electrospinning machine for electrospinning, and electrospinning was performed for 12h under the conditions of voltage 20kV, propulsion speed 0.02mL / min, receiving distance 15cm, and roller speed 300r / min to prepare PAN nanofibers, and the prepared PAN nanofibers were dried to remove excess DMF to prevent PAN nanofiber adhesion, and the preparation of PAN nanofibers was completed. The dried PAN nanofibers were completely immersed in the wastewater from the drilling and blasting tunnel construction, and the PAN nanofibers were used to remove nitrates. The immersion time was 3 hours. After the reaction was completed, the PAN nanofibers were taken out.

[0048] The PAN nanofibers that have adsorbed nitrate ions are first soaked in dilute hydrochloric acid to remove excess iron powder, and then dried in an oven at 80°C for 10 hours. The dried PAN nanofibers are then placed in a ball mill for grinding, wherein the ball mill speed is 150 r / min, the ball-to-material mass ratio is 40:1, and the ball milling time is 10 minutes. After the ball milling is completed, the PAN powder is separated and sieved through a 200-mesh sieve to complete the recycling of PAN.

[0049] This comparative example is basically the same as Example 1, except that:

[0050] In the process of preparing PAN nanofibers, the amount of DMF added is 9.6 g, and the amount of PAN white powder added is 0.4 g, wherein the mass fraction of PAN is 4%. After adding PAN, in the process of removing nitrate, the soaking time is 3 h. In the process of recovering PAN nanofibers, the ball-to-material ratio is 40:1, and the ball mill speed is 150 r / min. The other conditions are the same as those in Example 1.

[0051] like Figure 2 It can be seen that the nitrate removal rate and PAN recovery rate of Comparative Example 1 are both low, because the PAN mass fraction is low, the viscosity is low, and the diameter of the nanofiber is small, which leads to a decrease in the loading amount of iron powder and calcium-based montmorillonite. The immersion time is too short, which will lead to a decrease in the removal rate of nitrate in the water body. During the PAN recovery process, the ball-to-material ratio and the ball mill speed are low, which leads to the inability to fully grind PAN, resulting in a decrease in the PAN recovery rate.

[0052] Example 2

[0053] First, 9.2g DMF was added to a beaker, and 0.5g of submicron iron powder and 0.5g of submicron calcium montmorillonite were added to the DMF solution in turn, and ultrasonically dispersed, and then stirred for 1h to uniformly disperse the iron powder and calcium montmorillonite. 0.8g PAN white powder was weighed and added to the above solution, and stirred for 8h to completely dissolve PAN into a viscous liquid, and an electrospinning precursor solution was obtained, wherein the mass fraction of PAN was 8%. The electrospinning precursor solution was then placed in an electrospinning machine for electrospinning, and electrospinning was performed for 12h under the conditions of voltage 20kV, propulsion speed 0.02mL / min, receiving distance 15cm, and roller speed 300r / min to prepare PAN nanofibers, and the prepared PAN nanofibers were dried to remove excess DMF to prevent PAN nanofiber adhesion, and the preparation of PAN nanofibers was completed. The dried PAN nanofibers were completely immersed in the wastewater from the drilling and blasting tunnel construction, and the PAN nanofibers were used to remove nitrates. The immersion time was 12 hours. After the reaction was completed, the PAN nanofibers were taken out.

[0054] The PAN nanofibers that have adsorbed nitrate ions are first soaked in dilute hydrochloric acid to remove excess iron powder, and then dried in an oven at 80°C for 10 hours. The dried PAN nanofibers are then placed in a ball mill for grinding, wherein the ball mill speed is 300 r / min, the ball-to-material mass ratio is 100:1, and the ball milling time is 10 minutes. After the ball milling is completed, the PAN powder is separated and sieved through a 200-mesh sieve to complete the recycling of PAN.

[0055] This embodiment is basically the same as Embodiment 1, except that:

[0056] In the process of preparing PAN nanofibers, the amount of DMF added was 9.2 g, and the amount of PAN white powder added was 0.8 g, wherein the mass fraction of PAN was 8%.

[0057] Depend on Figure 2 It can be seen that the removal rate of nitrate is low, the mass fraction of PAN is low during the electrospinning process, the viscosity of the precursor solution is low, resulting in a smaller diameter of the nanofibers, and the loading amount of calcium-based montmorillonite and iron powder is low, resulting in a lower removal rate of nitrate.

[0058] Example 3

[0059] First, 8.5g DMF was added to a beaker, and 0.5g of submicron iron powder and 0.5g of submicron calcium montmorillonite were added to the DMF solution in turn, and ultrasonically dispersed, and then stirred for 1h to uniformly disperse the iron powder and calcium montmorillonite. 1.5g PAN white powder was weighed and added to the above solution, and stirred for 8h to completely dissolve PAN into a viscous liquid, and an electrospinning precursor solution was obtained, wherein the mass fraction of PAN was 15%. The electrospinning precursor solution was then placed in an electrospinning machine for electrospinning, and electrospinning was performed for 12h under the conditions of voltage 20kV, propulsion speed 0.02mL / min, receiving distance 15cm, and roller speed 300r / min to prepare PAN nanofibers, and the prepared PAN nanofibers were dried to remove excess DMF to prevent PAN nanofiber adhesion, and the preparation of PAN nanofibers was completed. The dried PAN nanofibers were completely immersed in the wastewater from the drilling and blasting tunnel construction, and the PAN nanofibers were used to remove nitrates. The immersion time was 12 hours. After the reaction was completed, the PAN nanofibers were taken out.

[0060] The PAN nanofibers that have adsorbed nitrate ions are first soaked in dilute hydrochloric acid to remove excess iron powder, and then dried in an oven at 80°C for 10 hours. The dried PAN nanofibers are then placed in a ball mill for grinding, wherein the ball mill speed is 300 r / min, the ball-to-material mass ratio is 100:1, and the ball milling time is 10 minutes. After the ball milling is completed, the PAN powder is separated and sieved through a 200-mesh sieve to complete the recycling of PAN.

[0061] This embodiment is basically the same as Embodiment 1, except that:

[0062] In the process of preparing PAN nanofibers, the amount of DMF added was 8.5 g, and the amount of PAN white powder added was 1.5 g, wherein the mass fraction of PAN was 15%.

[0063] like Figure 2It can be seen that the removal rate of nitrate is low. Due to the increase in the mass fraction of PAN during the electrospinning process, the viscosity of the solution increases, making the diameter of the electrospun nanofibers larger, and the iron powder and calcium-based montmorillonite are wrapped inside the nanofibers. The iron powder and calcium-based montmorillonite cannot fully contact the water body, resulting in a decrease in the nitrate removal rate.

[0064] Example 4

[0065] First, 9g of DMF was added to a beaker, and 0.5g of submicron iron powder and 0.5g of submicron calcium-based montmorillonite were added to the DMF solution in turn, and ultrasonically dispersed, and then stirred for 1h to uniformly disperse the iron powder and calcium-based montmorillonite. 1g of PAN white powder was weighed and added to the above solution, and stirred for 8h to completely dissolve PAN into a viscous liquid, thereby obtaining an electrospinning precursor solution, wherein the mass fraction of PAN was 10%. The electrospinning precursor solution was then placed in an electrospinning machine for electrospinning, and electrospinning was performed for 12h under the conditions of voltage 20kV, propulsion speed 0.02mL / min, receiving distance 15cm, and roller speed 300r / min to obtain PAN nanofibers, and the prepared PAN nanofibers were dried to remove excess DMF to prevent PAN nanofiber adhesion, thereby completing the preparation of PAN nanofibers. The dried PAN nanofibers were completely immersed in the wastewater from the drilling and blasting tunnel construction, and the PAN nanofibers were used to remove nitrates. The immersion time was 6 hours. After the reaction was completed, the PAN nanofibers were taken out.

[0066] The PAN nanofibers that have adsorbed nitrate ions are first soaked in dilute hydrochloric acid to remove excess iron powder, and then dried in an oven at 80°C for 10 hours. The dried PAN nanofibers are then placed in a ball mill for grinding, wherein the ball mill speed is 300 r / min, the ball-to-material mass ratio is 100:1, and the ball milling time is 10 minutes. After the ball milling is completed, the PAN powder is separated and sieved through a 200-mesh sieve to complete the recycling of PAN.

[0067] This embodiment is basically the same as Embodiment 1, except that:

[0068] In the process of removing nitrate from water by nanofiber material, the immersion time is 6h.

[0069] like Figure 2 It can be seen that the nitrate removal effect is reduced mainly because the immersion time is too short, resulting in a shorter contact time between the nanofibers and the water body, and the nitrate cannot be effectively removed.

[0070] Example 5

[0071] First, 9g of DMF was added to a beaker, and 0.5g of submicron iron powder and 0.5g of submicron calcium-based montmorillonite were added to the DMF solution in turn, and ultrasonically dispersed, and then stirred for 1h to uniformly disperse the iron powder and calcium-based montmorillonite. 1g of PAN white powder was weighed and added to the above solution, and stirred for 8h to completely dissolve PAN into a viscous liquid, thereby obtaining an electrospinning precursor solution, wherein the mass fraction of PAN was 10%. The electrospinning precursor solution was then placed in an electrospinning machine for electrospinning, and electrospinning was performed for 12h under the conditions of voltage 20kV, propulsion speed 0.02mL / min, receiving distance 15cm, and roller speed 300r / min to obtain PAN nanofibers, and the prepared PAN nanofibers were dried to remove excess DMF to prevent PAN nanofiber adhesion, thereby completing the preparation of PAN nanofibers. The dried PAN nanofibers were completely immersed in the wastewater from the drilling and blasting tunnel construction, and the PAN nanofibers were used to remove nitrates. The immersion time was 18 hours. After the reaction was completed, the PAN nanofibers were taken out.

[0072] The PAN nanofibers that have adsorbed nitrate ions are first soaked in dilute hydrochloric acid to remove excess iron powder, and then dried in an oven at 80°C for 10 hours. The dried PAN nanofibers are then placed in a ball mill for grinding, wherein the ball mill speed is 300 r / min, the ball-to-material mass ratio is 100:1, and the ball milling time is 10 minutes. After the ball milling is completed, the PAN powder is separated and sieved through a 200-mesh sieve to complete the recycling of PAN.

[0073] This embodiment is basically the same as Embodiment 1, except that:

[0074] In the process of removing nitrate from water by nanofiber material, the immersion time is 18h.

[0075] like Figure 2 It can be seen that the removal rate of nitrate is low. If the immersion time is too long, the nitrate ions adsorbed on the surface of calcium-based montmorillonite will detach and enter the water body. In addition, the iron powder in the nanofibers is easily oxidized, resulting in failure to react with nitrate ions in time. Excessive immersion time leads to a decrease in the removal rate of nitrate by nanofibers.

[0076] Example 6

[0077] First, 9g of DMF was added to a beaker, and 0.5g of submicron iron powder and 0.5g of submicron calcium-based montmorillonite were added to the DMF solution in turn, and ultrasonically dispersed, and then stirred for 1h to uniformly disperse the iron powder and calcium-based montmorillonite. 1g of PAN white powder was weighed and added to the above solution, and stirred for 8h to completely dissolve PAN into a viscous liquid, thereby obtaining an electrospinning precursor solution, wherein the mass fraction of PAN was 10%. The electrospinning precursor solution was then placed in an electrospinning machine for electrospinning, and electrospinning was performed for 12h under the conditions of voltage 20kV, propulsion speed 0.02mL / min, receiving distance 15cm, and roller speed 300r / min to obtain PAN nanofibers, and the prepared PAN nanofibers were dried to remove excess DMF to prevent PAN nanofiber adhesion, thereby completing the preparation of PAN nanofibers. The dried PAN nanofibers were completely immersed in the wastewater from the drilling and blasting tunnel construction, and the PAN nanofibers were used to remove nitrates. The immersion time was 12 hours. After the reaction was completed, the PAN nanofibers were taken out.

[0078] The PAN nanofibers that have adsorbed nitrate ions are first soaked in dilute hydrochloric acid to remove excess iron powder, and then dried in an oven at 80°C for 10 hours. The dried PAN nanofibers are then placed in a ball mill for grinding, wherein the ball mill speed is 200 r / min, the ball-to-material mass ratio is 50:1, and the ball milling time is 10 minutes. After the ball milling is completed, the PAN powder is separated and sieved through a 200-mesh sieve to complete the recycling of PAN.

[0079] This embodiment is basically the same as Embodiment 1, except that:

[0080] In the process of PAN nanofiber recovery, the ball-to-material ratio during ball milling was 50:1 and the ball mill speed was 200 r / min.

[0081] like Figure 2 It can be seen that the recovery rate of PAN is low, mainly because the ball material is relatively low and the ball mill speed is low, which cannot completely crush the nanofibers. During the screening process, a large amount of electrospinning base material PAN cannot pass through the sample sieve, resulting in a low recovery rate of PAN.

[0082] Example 7

[0083] First, 9g of DMF was added to a beaker, and 0.5g of submicron iron powder and 0.5g of submicron calcium-based montmorillonite were added to the DMF solution in turn, and ultrasonically dispersed, and then stirred for 1h to uniformly disperse the iron powder and calcium-based montmorillonite. 1g of PAN white powder was weighed and added to the above solution, and stirred for 8h to completely dissolve PAN into a viscous liquid, thereby obtaining an electrospinning precursor solution, wherein the mass fraction of PAN was 10%. The electrospinning precursor solution was then placed in an electrospinning machine for electrospinning, and electrospinning was performed for 12h under the conditions of voltage 20kV, propulsion speed 0.02mL / min, receiving distance 15cm, and roller speed 300r / min to obtain PAN nanofibers, and the prepared PAN nanofibers were dried to remove excess DMF to prevent PAN nanofiber adhesion, thereby completing the preparation of PAN nanofibers. The dried PAN nanofibers were completely immersed in the wastewater from the drilling and blasting tunnel construction, and the PAN nanofibers were used to remove nitrates. The immersion time was 12 hours. After the reaction was completed, the PAN nanofibers were taken out.

[0084] The PAN nanofibers that have adsorbed nitrate ions are first soaked in dilute hydrochloric acid to remove excess iron powder, and then dried in an oven at 80°C for 10 hours. The dried PAN nanofibers are then placed in a ball mill for grinding, wherein the ball mill speed is 400 r / min, the ball-to-material mass ratio is 150:1, and the ball milling time is 10 minutes. After the ball milling is completed, the PAN powder is separated and sieved through a 200-mesh sieve to complete the recycling of PAN.

[0085] This embodiment is basically the same as Embodiment 1, except that:

[0086] In the recycling process of PAN nanofibers, the ball-to-material ratio was 150:1 and the ball mill speed was 400 r / min.

[0087] like Figure 2 It can be seen that compared with Example 1, the recovery rate of PAN is reduced. The high ball-to-material ratio and high rotation speed cause the PAN nanofibers to be severely adhered during the ball milling process and are difficult to separate, resulting in a reduced recovery rate of PAN.

[0088] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for removing nitrates from wastewater from tunnel construction using a drilling and blasting method, characterized in that: The following steps are involved: Step 1, preparing electrospinning nanofibers: using DMF (N, N-dimethylformamide) as a solvent for nanofiber precursors and PAN (polyacrylonitrile) as an electrospinning base material, first taking DMF and adding it to a container, and taking submicron iron powder and submicron calcium-based montmorillonite, the mass ratio of iron powder to calcium-based montmorillonite is 1 to 9:3, and adding them to the DMF solution in sequence, and ultrasonically dispersing, and then stirring to make the iron powder and calcium-based montmorillonite evenly dispersed; weighing PAN powder, adding it to the above solution, stirring, so that PAN is completely dissolved into a viscous liquid, that is, obtaining an electrospinning precursor solution, the mass fraction of PAN in the electrospinning precursor solution is 5-15%, and then putting the obtained solution into an electrospinning machine for electrospinning to prepare PAN nanofibers, drying the prepared PAN nanofibers, removing excess DMF, and preventing the PAN nanofibers from sticking; Step 2, removing nitrates from wastewater from tunnel construction using the drilling and blasting method: completely immersing the dried PAN nanofibers in the wastewater from tunnel construction using the drilling and blasting method, and taking out the PAN nanofibers after immersing for a period of time.

2. The method for removing nitrates from drilling and blasting tunnel construction wastewater according to claim 1, characterized in that: The method for removing nitrate from wastewater from tunnel construction by drilling and blasting also includes step 3, recycling PAN: soaking the used PAN nanofibers in dilute hydrochloric acid to remove excess iron powder, then drying them in an oven, and then putting the dried PAN nanofibers into a ball mill for grinding. After the ball milling is completed, the PAN powder is ground and separated and sieved, thereby completing the recycling of PAN.

3. The method for removing nitrates from drilling and blasting tunnel construction wastewater according to claim 2, characterized in that: In the step 1, the prepared PAN nanofibers are dried in an oven at a temperature of 80° C.; in the step 3, the used PAN nanofibers are dried in an oven at a temperature of 80° C. for a drying time of 10 hours.

4. The method for removing nitrates from drilling and blasting tunnel construction wastewater according to claim 2, characterized in that: In the step 3, when the powder is put into the ball mill for grinding, the speed of the ball mill is set to 200-400 r / min, the ball-to-material ratio is set to 50-150:1, and the ball milling time is set to 5-15 min.

5. The method for removing nitrate from drilling and blasting tunnel construction wastewater according to claim 1, characterized in that: In the step 1, the mass ratio of DMF: iron powder: calcium-based montmorillonite is 17-19:1:

1.

6. The method for removing nitrates from drilling and blasting tunnel construction wastewater according to claim 1, characterized in that: In the step 1, the mass ratio of the added amount of PAN powder to the sum of the mass of iron powder and calcium-based montmorillonite is 0.5-1.5:

1.

7. The method for removing nitrate from drilling and blasting tunnel construction wastewater according to claim 1, characterized in that: In the step 1, the voltage of the electrospinning machine is set at 15 to 25 kV, the propulsion speed is set at 0.01 to 0.03 mL / min, the receiving distance is set at 10 to 20 cm, and the roller speed is set at 200 to 500 r / min.

8. The method for removing nitrates from drilling and blasting tunnel construction wastewater according to claim 1, characterized in that: In the step 1, the mixture is stirred for 0.5 to 2 hours after ultrasonic dispersion, and stirred for 4 to 16 hours after adding PAN powder.

9. The method for removing nitrate from drilling and blasting tunnel construction wastewater according to claim 1, characterized in that: In step 2, the soaking time is 6 to 18 hours.

Citation Information

Patent Citations

  • Porous nanometer zero-valent iron and porous nanometer zero-valent iron composite material

    CN105081305A

  • Preparation method and application of zero-valent nano-iron supported polyacrylonitrile membrane composite material

    CN106423096A

  • Preparation method of polyfunctional group modified PAN nanofiber high-efficiency adsorption material

    CN118022700A